Penguatan Civic Literacy dalam Membentuk Ketahanan Guru PPKN - Tiara, Monica; Irwan, Irwan; Muhajir, Muhajir (Journal of Civic Education, 2024)
One of the challenges in Indonesia’s education is civic literacy. The concept of civic literacy can be a filter for citizens in dealing with various civic issues, especially in the field of education. Therefore, strengthening civic literacy needs to be given to civic education teachers to shape students into global-minded citizens. This article aims to analyze the strengthening of civic literacy in building the resilience of civics teachers, especially in facing post-pandemic era. This research was analyzed using qualitative methods with high school civic education teachers in Padang City as research informants. Data collection techniques were carried out by distributing digital questionnaires, observation and interviews. The research results show that civic literacy plays an important role in strengthening teacher resilience. Civic literacy helps teachers sort information according to their mental and physical needs to adapt to post-pandemic learning. Through civic literacy, teachers are able to link civic issues with learning material and provide space for students to think critically. At the end of the research, it was revealed that strengthening civic literacy in building the resilience of civic education teachers in post-pandemic conditions has implications for increasing teacher self-confidence and teacher professional competence.